2016
DOI: 10.14210/bjast.v20n2.8575
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional profile of toasted canavalia ensiformis seed and its potetial as partially replacement for soybean in the diet of clarias gariepinus

Abstract: Feed procurement, processing, and analysis.Matured seeds of C. ensiformis were collected from Assakio in Lafia Nasarawa State Nigeria. The other ingredients, soybean meal, yellow maize meal, fish meal, vitamin and mineral premises were obtained from the modern market in Makurdi (the Benue State capital). The seeds of soybean and C. ensiformis were toasted to remove antinutritional factors. Toasting was not timed, but the seeds were visually observed for browning (an indication of complete toasting process acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
4
4
3
Order By: Relevance
“…This is in line with the hypothesis of Abbas () and Manjappa, Keshavanath, and Gangadhara () that nutrient utilization in a diet and its retention in fish carcass are related to both the dietary protein levels and the availability of non‐protein energy sources with a lower inclusion of dietary fiber. This finding is similar to earlier studies, where soybean meal was replaced by other plants in the practical diets of tropical fish species (Fagbenro, Adeparusi, & Jimoh, ; Azaza, Mensi et al, ; Azaza, Wassim et al., ; Tiamiyu, Okomoda, & Akpa, ). Some earlier studies revealed an insignificant effect of dietary soybean substitution (Lin, Mai, & Tan, ; Van Vo et al., ; Wang, Kong, Li, & Bureau, ), while others revealed a significant increase (Fagbenro et al., ; Okomoda, Tiamiyu, & Uma, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in line with the hypothesis of Abbas () and Manjappa, Keshavanath, and Gangadhara () that nutrient utilization in a diet and its retention in fish carcass are related to both the dietary protein levels and the availability of non‐protein energy sources with a lower inclusion of dietary fiber. This finding is similar to earlier studies, where soybean meal was replaced by other plants in the practical diets of tropical fish species (Fagbenro, Adeparusi, & Jimoh, ; Azaza, Mensi et al, ; Azaza, Wassim et al., ; Tiamiyu, Okomoda, & Akpa, ). Some earlier studies revealed an insignificant effect of dietary soybean substitution (Lin, Mai, & Tan, ; Van Vo et al., ; Wang, Kong, Li, & Bureau, ), while others revealed a significant increase (Fagbenro et al., ; Okomoda, Tiamiyu, & Uma, ).…”
Section: Discussionsupporting
confidence: 91%
“…Beyond this point, growth and nutrient utilization was reduced significantly. A similar observation was reported by Tiamiyu, Okomoda, & Akpa () in African catfish fed toasted jackbean meal. Craig and Helfrich () noted that protein is used for growth when adequate levels of fat and carbohydrates are present in the diet.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The soybeans purchased were toasted at 100°C for 30 min to inactivate the anti‐nutritive factors present following the method of Tiamiyu et al. (). Toasting was done by continuously stirring the seeds in fine texture sand heated on a hot plate.…”
Section: Methodsmentioning
confidence: 99%
“…Research has also shown that they represent good dietary protein and energy sources for fish (Jauncey, ). The genus Canavalia (Jack bean) comprises 48 species of underutilized legumes indigenous and widely distributed in the tropics (Tiamiyu, Okomoda, & Akpa, ). It is rarely eaten by man and has a total yield of up to 2.5 tons·ha −1 under optimal agronomic conditions (Okonkwo & Udedibie, ).…”
Section: Introductionmentioning
confidence: 99%